Thyroid hormone receptor subtype-specific function in controlling organ-specific developmental timing and rate during Xenopus development - Tanizaki, Yuta; Shi, Yun-Bo (Frontiers in Endocrinology, 2025)
Thyroid hormone (T3) is essential for vertebrate development as animals fail to develop into adults in the absence of T3. T3 is particularly critical for postembryonic development. This is a period around birth in mammals when most organs mature as plasma T3 level peaks. Unlike embryogenesis, postembryonic development has not been well-studied in mammals due to the difficulty to manipulate mammalian embryos and neonates. In contrast, anuran metamorphosis involves drastic transformations of essentially every organ/tissue of a tadpole and can be easily manipulated externally without maternal influence. In addition, most changes during metamorphosis resemble organ-maturation during postembryonic mammalian development. Thus, metamorphosis offers a unique and highly advantageous opportunity for studying postembryonic vertebrate development. Studies on the metamorphosis of Xenopus laevis and Xenopus tropicalis, two highly related species have offered significant insights on the function of thyroid hormone receptors in development. Here we will review some of these studies, with particular emphasis on recent genetic and genome-wide molecular analyses in the diploid species Xenopus tropicalis, that support a dual function model of TR, involving distinct, organ-specific roles of TRα and TRβ, the only known TR genes in all vertebrates.